Robot-assisted needle insertion for venous catheterization - Pasternak,Jacyr (2015)
Vein access can be challenging for a variety of patients. The development of robots-assisted central or peripheral veins puncture would facilitate life of health professionals and patients. New robots are under development for this purpose and probably they will become available for practical use in the near future. These techniques may decrease significantly the cost of medicine, which currently uses less informatics resources than other industries.